WEB-Based Decision Support System for Mobile Selection using the Simple Additive Weighting Method - Agnesdea Meiti Suroso (Journal of Intelligent Decision Support System (IDSS), 2021)
Along with the development of mobile phones in Indonesia, people from various professions are very dependent on mobile phones. Problems arise when these developments are not accompanied by a system that supports the selection of the right cellphone and according to the criteria of each user. A web-based decision support system for the selection of mobile phones using the simple additive weighting method is a web-based information system that can be used to assist prospective mobile phone buyers in choosing the right cellphone and according to the criteria. In this system the user will give weight to the main criteria, namely price, brand, depreciation, RAM, camera, screen, battery, and features. The weighting must be with a total of 100 percent.